سبع طوال اور مئین میں سورتوں کے تناسق موضوعی کا ایک جائزہ تفسیر معارف القرآن کاندھلوی کی روشنی: The Thematic Connection between Surahs in the Seven Tiwal and Miyin An Analysis in the Light of Tafisr Ma'arif-ul-Quran Kandhalvi - Bilal Khan; Dr Riaz Ahmed Siddiqui; Noushad Ahmad (Al Manhal Research Journal, 2024)
This article explores the thematic connections between surahs in the Quranic, with a specific focus on the Tiwal and Miyin sections (Surah Al-Fatiha to Surah Fatir). The Quran's revelatory order and its compiled mushaf order have sparked scholarly interest in understanding the intentional arrangement of surahs. Muslim scholars widely acknowledge the mushaf order as tawqifi, implying divine guidance. Therefore, this study seeks to uncover the underlying thematic relationships between adjacent surahs. Utilising Muhammad Idris Kandhalvi's insightful commentary in Ma'arif al-Quran, this research elucidates the deliberate arrangement of selected surahs within the Tiwal and Miyin sections. By examining Kandhalvi's exposition, this article aims to contribute to a deeper understanding of the Quran's structural coherence and the interconnectedness of its thematic content.